The Influence of Human-AI Interaction in the Decision-Making Process in the Health Sector: A Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Armansyah, Muhammad (Arkus, 2024)
Artificial intelligence (AI) plays an increasingly important role in the health sector, including in the decision-making process. Human-AI interaction can help doctors diagnose diseases, provide treatment recommendations, and improve the quality of patient care. This research uses experimental studies to investigate the influence of human-AI interactions in the decision-making process in the health sector. Two groups of doctors were included: a group that used AI to aid decision making and a control group that did not use AI. The research results showed that the group of doctors who used AI had better performance in terms of diagnostic accuracy, time efficiency and patient satisfaction. Human-AI interaction can help doctors make better decisions and improve the quality of patient care.